2016
DOI: 10.1590/0103-9016-2015-0051
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid of dairy foods is affected by cows’ feeding system and processing of milk

Abstract: The distribution of conjugated linoleic acid (CLA) in dairy products commercially available in Chile is poorly understood. This study aimed to assess the content of CLA in dairy cow products from Chile and the effect of processing fresh milk into dairy products. Samples of raw milk were categorized into two groups based on the animal feeding system utilized by the dairy farm: 1) grazing based systems (Los Lagos region); and 2) housing systems using total mixed ration (TMR) diets (Los Angeles region). Simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…In this study, rumenic acid varied between 68-71% of the total CLA. Previous work indicated that the C18:2 cis-9 trans-11 content in mozzarella cheese can account for more than 80% of the CLA in milk (Romano et al, 2011), but factors, such as milk origin and processing, may determine variations (Martini et al, 2016;Ruiz et al, 2016).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…In this study, rumenic acid varied between 68-71% of the total CLA. Previous work indicated that the C18:2 cis-9 trans-11 content in mozzarella cheese can account for more than 80% of the CLA in milk (Romano et al, 2011), but factors, such as milk origin and processing, may determine variations (Martini et al, 2016;Ruiz et al, 2016).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The cows' diet is the key to modifying the nutritional value of milk. Pasture-based feeding of cows has been shown to positively influence the fatty acid profile of milk [5][6][7]. However, on large-scale farms keeping cows with high production potential, animal feeding is usually mainly based on hay and maize silage year-round.…”
Section: Introductionmentioning
confidence: 99%
“…About 70% of the fatty acids in milk triacylglycerols are saturated, 25% are monounsaturated fatty acids (MUFA), and 5% are polyunsaturated fatty acids (PUFA) (Lopes et al, 2016;Abd El-Salam & El-Shibiny, 2020). Studies have shown nutritional components of milk fat, with an emphasis on conjugated linoleic acid (CLA), which consists of a group of fatty acids found predominantly in the milk (Agiral et al, 2020) and meat of ruminant animals, such as cows' (Ruiz et al, 2016), sheep (Nudda et al, 2014, Madruga et al, 2020, and goat (Apás et al, 2015). In milk, fatty acids can come from the diet, transported to the mammary gland or synthesized by the mammary epithelial cells (Vargas-Bello-Perez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%